Bioethics and rehabilitation - Saad Hossne, William; Zaher, Vera Lúcia (O Mundo da Saúde, 2006)
The work discusses the importance of considering different references of bioethics when we focus on rehabilitation. It calls the attention to the question of bioethical calls that in a way can deprive it of its distinctive characteristics, which, in being ethical, supposes conflict resolution and option for values. Bioethics questions and challenges on the field of rehabilitation involve patients, the team of health professionals, the family and society, including problems that range from the technical, professional, educative, and sociological to econometrical and legal ones. They are all important actors and sectors and sometimes this or that one has a temporary primacy. Stemming from this series of reflections the theme Bioethics and Rehabilitation implies the discussion of ethical questions both in the formation of health professionals, in the organization and the professional supplying of services, the organization and the institutional supplying of services and in the economic-social system. Vulnerability, discrimination, stigmatization, equity, justice, pre- conception, solidarity and assistancialism are references that organize this article beyond the literature review on the subject.